Surgical repair of thoraco-lumbar vertebral fracture-luxations in eight cats using screws and polymethylmethacrylate fixation - Vallefuoco, R.; Manassero, M.; Leperlier, D.; Scotti, S.; Viateau, V.; Moissonnier, P. (Veterinary and Comparative Orthopaedics and Traumatology, 2014)
Objective: To report our clinical experience in the surgical treatment of feline thora-columbar vertebral fracture-luxations using optimal safe implantation corridors as previously described in vitro.Study design: Retrospective clinical study.Materials and Methods: Medical records and radiographs of cats with vertebral fracture- luxations stabilized by screws and polymethylmethacrylate (PMMA) using optimal safe implantation corridors between 2009 and 2011 were reviewed. For each patient the data included: signalment, cause of vertebral fracture-luxations, presence of concurrent injuries, pre- and postoperative neurological grade, surgical treatment, imaging findings, and clinical outcome with short-term (2 weeks) and long-term (12 months) follow-up.Results: Eight cats with vertebral fracture-luxations involving the lumbar (L)(n = 5), the thoracic (T) spinal segments (n = 2), or the thoraco-lumbar junction (n = 1) were included in the study. Screws and PMMA were used bilaterally in five cats and unilaterally in three cats. No surgical intra-operative complications using the defined corridors were recorded. Implant failure followed by spontaneous recovery was recorded in one case. Two cats died in the postoperative period (≤4 days). The short-term and long-term clinical outcome was excellent in four out of eight cats and satisfactory in two out of eight cats.Conclusion and Clinical relevance: This pilot study demonstrates the clinical applicability of optimal safe implantation corridors for stabilization of feline thoraco-lumbar vertebral fracture-luxations with screws and PMMA. This technique can be used with limited risks of iatrogenic injuries for stabilization of vertebral fracture-luxation localized between T11-L4.
Keywords: Cat; vertebral; fracture; implantation corridor; luxation